Comparison of the Institute for Credentialing Excellence Multi-Organization Survey of Certificants. (28th October 2021) - Francis, E; Harrington, A; Eschliman, P J; Harrington, S; Duzan, D; Tanabe, P
Abstract: Introduction/Objective: The Institute for Credentialing Excellence (ICE) conducted a study to measure the value that credential holders place on certification, collecting survey data from a large sample of more than 12, 000 credential holders representing six organizations (4 of which were healthcare). In May of 2019, ASCP BOC sent the survey to 47, 384 individuals certified within the last 5 years. Of those who received the survey; 2, 038 completed the 80 required questions. A comparison of survey data provided an overview of the top five differences in the full survey data (n=9, 407) and the data from respondents credentialed by ASCP BOC (n = 2, 038 or 22% of full survey respondents) and highlighted the primary reasons individuals pursue certification. Methods/Case Report: This survey sought to define certificants' attitudes toward and experiences with certification. Survey questions were grouped by four primary subject areas: The Value of Certification for Respondents' Professions The Value of Certification for Employers The Value of Certification Outside the U.S. and Canada The Value of Certification for Certificants - Responses of themed queries of full survey data and BOC survey data were viewed side by side and averages, standard deviations and medians were calculated. The top 5 items indicating the highest difference from the full survey data results were highlighted. - Ranked primary motivational factors for the pursuit of certification were viewed side-by-side. Results (if a Case Study enter NA): Based on a side-by-side comparison of full survey data and BOC survey data, only minor differences were noted with the exception of the question pertaining to the perceived value of recertification. Both differences and items of agreement were highlighted. The top 10 reasons for seeking certification were the same amongst both the full survey and ASCP BOC survey respondents, with minor differences in priority order. Conclusion: With the exception of the question regarding the value of recertification, discrepancies noted were minor. On most questions pertaining to the various benefits of certification, a majority of respondents gave a positive response about certification and its relationship to beneficial outcomes for their professions, employers, or themselves. It is clear that certificants place a high value on certification and believe that certification provides a number of valuable benefits.